2017
DOI: 10.1371/journal.pone.0171137
|View full text |Cite
|
Sign up to set email alerts
|

Statin improves survival in patients with EGFR-TKI lung cancer: A nationwide population-based study

Abstract: Long-term use of statins has been reported to reduce the risk of death in patients with lung cancer. This study investigated the effect of statin use among patients with lung cancer receiving epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKIs) therapy. A nationwide, population-based case-control study was conducted using the Taiwan National Health Insurance Research Database. From January 1, 1997 to December 31, 2012, a total of 1,707 statin and 6,828 non-statin matched lung cancer cohorts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 40 publications
2
70
0
Order By: Relevance
“…23,26,48 Total cellular cholesterol was shown to be upregulated in gefitinib resistant cells. 18,20,27,28 Several studies have shown that elevated levels of mitochondrial cholesterol in cancer cells may be able to protect cancer cells against mitochondrial apoptosis by reducing the ability of Bax to insert into the mitochondrial membrane thus impairing MOMP and the release of cytochrome c. [29][30][31] To our knowledge, no previous studies have linked this phenomenon to EGFR TKI exposure and resistance. The cells were not under exposure to gefitinib when cholesterol was isolated, but rather they were comparing levels between the different cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…23,26,48 Total cellular cholesterol was shown to be upregulated in gefitinib resistant cells. 18,20,27,28 Several studies have shown that elevated levels of mitochondrial cholesterol in cancer cells may be able to protect cancer cells against mitochondrial apoptosis by reducing the ability of Bax to insert into the mitochondrial membrane thus impairing MOMP and the release of cytochrome c. [29][30][31] To our knowledge, no previous studies have linked this phenomenon to EGFR TKI exposure and resistance. The cells were not under exposure to gefitinib when cholesterol was isolated, but rather they were comparing levels between the different cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR TKIs have been shown to mediate their apoptotic effects via inhibition of Akt/Erk signaling, which downregulates anti-apoptotic Bcl-2 family proteins that are responsible for binding and inhibiting Bax and Bak, which once free, can cause MOMP and activate apoptotic cell death. 18,20,27,28 Several studies have shown that elevated levels of mitochondrial cholesterol in cancer cells may be able to protect cancer cells against mitochondrial apoptosis by reducing the ability of Bax to insert into the mitochondrial membrane thus impairing MOMP and the release of cytochrome c. [29][30][31] To our knowledge, no previous studies have linked this phenomenon to EGFR TKI exposure and resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential confounding medical conditions, including type 2 diabetes mellitus (T2DM), hypertension, hypercholesterolemia, pneumonia, pulmonary tuberculosis (TB), asthma, chronic obstructive pulmonary disease (COPD), coal worker pneumoconiosis, asbestosis, toxic effect of arsenic, human immunodeficiency virus (HIV), and smoking were adjusted for in the analysis. Furthermore, prescription of medications known to moderate the risk for lung cancer (e. g., aspirin, nonsteroidal anti-inflammatory drugs [NSAIDs], and statins) was controlled for in the analysis [29][30][31][32][33]. Potential confounding variables including socioeconomic status (SES) was adjusted for by using income and urbanization of living area as proxies in the model.…”
Section: Confounding Factors/assessment Of Health Statusmentioning
confidence: 99%